O devir da gestão de pessoas pós-pandemia da COVID-19 - Ana Paula, Moura Caetano (Universidade Federal do Tocantins, 2023)
This research aimed to discuss the evolution of people management after the Covid- 19 pandemic. Contemporary aspects of people management were worked on, tracing a historical path since its beginning, but mainly in the period of the Covid-19 pandemic (2019-2021), bringing recent articles as a reference. In this way, as a contribution to the theme, a discussion was developed on how the people management scenario has changed, what were the challenges faced by managers, and what came to stay in the post-pandemic. The research was qualitative, exploratory, using the technique of content analysis. It started with 3 thematic categories: 1) changes in people management during the pandemic; 2) difficulties faced by managers; 3) the future of post-pandemic people management. However, for the research theme, 25 (twenty-five) webinars/lives from the ABRH-Brasil and RH pra você channels were relevant, from October 2020 to October 2022. There were 48 hours of content analyzed, with 26 hours referring to the webinars/lives that met the proposed objectives. From the analyzed content, the main changes that occurred during and after the pandemic can be deduced; the challenges faced by managers and the future of people management, including: new work formats, hybrid, remote; humanized leadership; mental health care; digital transformation; diversity and inclusion.